Off-label use of recombinant factor VIIa for neonatal pulmonary hemorrhage; a single-center experience - Özge Serçe Pehlevan; Ayna Atayeva; Ayla Günlemez; Sibel Balcı (The Turkish Journal of Pediatrics)
Background. Pulmonary hemorrhage (PH) leads to acute and catastrophic deterioration in neonates, and there is no curative treatment available. Off-label use of recombinant Factor VIIa (rFVIIa) is a promising treatment to control bleeding. The aim of this study was to investigate the efficacy and safety of rFVIIa in neonatal massive PH.